Peran Pendidikan Nonformal dalam Meningkatkan Kualitas Sumber Daya Manusia di Indonesia : (Studi Literatur) - Khusnul Khotimah Dewi; Ajat Rukajat; Chairil Fajar Hadiansyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to analyze the role of non-formal education in improving the quality of human resources in Indonesia. Non-formal education serves as an alternative and complement to formal education by providing broader access to learning opportunities for people from various social and economic backgrounds. This research employed a qualitative approach using a library research method through the collection of data from scientific journals, books, and policy documents related to non-formal education. The findings indicate that non-formal education significantly contributes to improving community skills, work competencies, productivity, and competitiveness. The most influential programs include equivalency education, skills training, entrepreneurship education, and life skills education. In addition, non-formal education helps reduce unemployment and improve community welfare through workforce development and entrepreneurship empowerment. Non-formal education also supports the concept of lifelong education by offering flexible learning opportunities for all age groups. However, its development still faces challenges such as limited facilities, insufficient funding, uneven educator quality, and adaptation to digital technology. Therefore, stronger government support and community-based program development are needed to optimize the role of non-formal education in improving the quality of Indonesia’s human resources.